Passport of Geology Museum: a Description Analysis on Pupils’ Worksheet - Kuswanto Kuswanto; Ai Sutini; Dede Trie Kurniawan; Rendi Restiana Sukardi (Universitas Sebelas Maret, 2022)
Kindergarten and elementary school students' activities of observing, understanding, and interpreting scientific objects at the Geology Museum have the opportunity to build various thinking skills. This can be done if students are given probing questions that are able to construct their knowledge. Therefore, the study aims to describe a prototype called the Passport of the Geology Museum and opinions from experts, teachers, and pupils. The research was descriptive that told the passport in detail. The instrument used in this study was observation field notes and interview. The result showed that the passport had many interesting features that open many opportunities for pupils to write down their observation activities in the museum. Pupils were able to tell their feeling and interest in the museum. Besides, both experts and teachers gave positive feedback on the passport. They told that passport in the Geological Museum was so helpful. It was a platform to guide pupils in finding and optimizing their sensory observation. Pupils were also very happy to use passports because it was understandable. The passport of the Geological Museum is very useful and helpful for both teachers and pupils.